A shadow like a leopard - Levoy, Myron (New York : Harper & Row, 1981)
A street-punk poet and an old painter form a friendship and confront their fears.
5.9
7-10.
Keywords: Artists -- Fiction; Friendship -- Fiction; Gangs -- Fiction; Friendship -- Fiction